2018
DOI: 10.1590/s0102-053620180303
|View full text |Cite
|
Sign up to set email alerts
|

Performance of processing tomatoes under different supply levels of crop evapotranspiration

Abstract: Irrigation management is essential to promote appropriate plant growth and guarantee production and quality of the tomatoes for processing, increases the efficiency of nutrients use and contributes to ensure the sustainability of the production chain. This study was installed to evaluate productive performance of two processing tomato hybrids submitted to five water depths under drip irrigation system. Five levels of crop evapotranspiration (ETc) replacement (60%, 100%, 140%, 180% and 220%) and two tomato hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
(18 reference statements)
3
4
0
1
Order By: Relevance
“…For the longitudinal and equatorial diameter, the increase was directly proportional to the increase in the volume of water applied. The linear equation models obtained in this study are like those observed by other authors evaluating tomatoes' horticultural responses to different irrigation levels [42][43][44][45][46].…”
Section: Fruit Qualitysupporting
confidence: 82%
See 1 more Smart Citation
“…For the longitudinal and equatorial diameter, the increase was directly proportional to the increase in the volume of water applied. The linear equation models obtained in this study are like those observed by other authors evaluating tomatoes' horticultural responses to different irrigation levels [42][43][44][45][46].…”
Section: Fruit Qualitysupporting
confidence: 82%
“…In the present study, a higher efficiency was founded for the treatment that applied a water depth of 572.12 mm. Silva et al [42] obtained greater efficiency in water use in treatments that applied water depth between 504 and 666 mm, while [51] found greater water use efficiency in the treatment that applied 582.7 mm. Other studies with tomato crops grown in different water depths in greenhouses [60,61] have shown that water deficit at different growth stages can directly affect the crop, significantly reducing plant growth and fruit yield.…”
Section: Number Of Irrigation Events Fruit Yield and Water Use Efficiencymentioning
confidence: 97%
“…According to Patanè et al (2011), deficit irrigations during the vegetative phase or from flowering, associated with longer periods of suspension of irrigation before fruit maturation, increased the content of total soluble solids of the fruits, with lower yield losses. Similar results were observed in Brazil (Moreira et al, 2012;Silva et al, 2018;Silva et al, 2019) and other countries (Wang et al, 2015;Wang & Xing, 2017;Samui et al, 2020), when was possible to conclude that the water deficit elevates the total soluble solids content and the acidity of tomato fruit. However, this procedure tends to reduce the yield and fruits size of the crop due to water stress (Soares et al, 2013;Morales et al, 2015;Rebouças Neto et al, 2017;Viol et al, 2018).…”
Section: Introductionsupporting
confidence: 84%
“…After harvest, 30 ripe fruits of each subplot were randomly chosen for postharvest evaluations in the laboratory. With these 30 ripe fruits, the average fruit mass (AFM, g per fruit) using a precision scale of 1 g, the shape of the fruit through the transverse diameter (TD, mm) and longitudinal diameter (LD, mm) was measured with a digital caliper, as proposed by Silva et al (2018).…”
Section: Methodsmentioning
confidence: 99%
“…In Brazil, the states of Goiás, São Paulo, and Minas Gerais have the largest areas of tomato cultivation and produce high quantities for industrial processing (IBGE 2017). The increase in tomato yields in recent years was due to the favorable cultivation conditions in the cerrado region (Goiás and Minas Gerais), where mechanical operations can be used more intensely, facilitating e.g., transplanting and harvesting (Peixoto et al 2017a, Silva et al 2018, Almeida Neta et al 2020. It is commonly acknowledged that hybrids and commercial lines should have: a) a high yield potential, b) concentrated maturation period, c) long durability of mature fruits on the plant, d) multiple disease resistance, e) a good canopy cover, f) smaller fruits (SST), and g) higher flesh firmness (Peixoto et al 2017a, Peixoto et al 2017b).…”
Section: Introductionmentioning
confidence: 99%